CrgA Protein Represses AlkB2 Monooxygenase and Regulates the Degradation of Medium-to-Long-Chain n-Alkanes in Pseudomonas aeruginosa SJTD-1 - Ji, Nannan; Wang, Xiuli; Yin, Chong; Peng, Wanli; Liang, Rubing (Frontiers in Microbiology, 2019)
AlkB monooxygenases in bacteria are responsible for the hydroxylation of medium- and long-chain n-alkanes. In this study, one CrgA protein of Pseudomonas aeruginosa SJTD-1, a member of LysR family, was proved to regulate AlkB2 monooxygenase and the degradation of medium-to-long-chain n-alkanes (C14-C20) by directly binding to the upstream of alkB2 gene. Two specific sites for CrgA binding were found in the promoter region of alkB2 gene, and the imperfect mirror repeat (IIR) structure was proved critical for CrgA recognition and binding. Hexadecyl CoA and octadecyl CoA could effectively release the CrgA binding and start the transcription, implying a positive regulation of metabolic intermediate. In the presence of medium-to-long-chain n-alkanes (C14-C20), deletion of crgA gene could enhance the transcription and expression of AlkB2 monooxygenase significantly; and in n-octadecane culture, strain S1∆alkB1&crgA grew vigrously than strain S1∆alkB1. Almost no regulation of CrgA protein was observed to alkB1 gene in vitro and in vivo. Therefore, CrgA acted as a negative regulator for the medium-to-long-chain n-alkane utilization in P. aeruginosa SJTD-1. The work will promote the regulation mechanism study of n-alkane degradation in bacteria and help the bioremediation method development for petroleum pollution.